CNA pulsations and related phenomena near L ~ 6 - Sato, Natsuo; Shibuya, Senkichi; Maezawa, Kiyoshi; Higuchi, Yoshihiro (1985)
P(論文) Quasi-periodic variation of cosmic radio noise absorption (called CNA pulsation), measured by a fast-response 30 MHz riometer at Syowa Station in Antarctica (L∿6), was examined. CNA pulsations with the period of 10-500s are observed mostly during morning hours. Most of the CNA pulsations are associated with magnetic pulsations and quasi-periodic (QP) VLF emissions. The examination of the relationships among CNA pulsations, magnetic pulsations and QP emissions, using the cross correlation analysis method, shows that some CNA pulsations with the period of 10-500s are well related to magnetic pulsations and QP emissions. In these cases CNA pulsations are more correlated with the D component of magnetic pulsations than with the H component. It is also shown that the phase of the CNA pulsations lags behind QP emissions by 60-120 degrees is independent of the pulsation period. departmental bulletin paper